Development of Home Care Guidelines for the Caregivers of the Patients Being Discharged with Spinal Cord Injury - Kaur, Navdeep; Singh, Neena Vir; Kaur, Sukhpal; Chabra, Rajesh (Indian Journal of Neurosurgery, 2015)
Background After spinal cord injury (SCI), victims may become partially or fully dependent on the caregivers. After getting discharge from the hospital, they are cared by their caregivers. Often patients return to hospital with serious complications owing to inadequate knowledge of the caregivers. So, it is essential to meet the informational needs of the caregiver regarding home care.Objective The aim of this study is to develop home care guidelines for the caregivers of the patients being discharged with SCI.Method The study was conducted in five phases. The blueprint of the home care guidelines was prepared. Face and content validity of the home care guidelines were done using the Delphi technique. An observational checklist was prepared from the final draft of the guidelines. The guidelines were found feasible after conducting a pilot study on five caregivers. To calculate the reliability of the guidelines, 30 caregivers were taught as per developed guidelines and were observed while caring for their patients by checklist. Reliability was calculated using Cronbach α coefficient.Results The checklist showed Cronbach α of 0.91. Guidelines were found to be feasible and reliable. Guidelines were developed in two languages: English and Hindi.Conclusion The home care guidelines are valid and reliable. Guidelines enable caregivers to provide the best possible care to their patient at home to prevent development of complications.
Keywords: SCI; home care guidelines; caregiver